PENGEMBANGAN UMKM B&B SNACK DESA SAWAHAN KABUPATEN REMBANG MELALUI GOOGLE MAPS DAN PAPAN PETUNJUK ARAH - Miftah, Syadida Elena Miftah; Sari, Dian Anita; Ni’mah, Nafisatun; Sodiq, Fajar (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Most MSMEs, including B&B Snack MSMEs, have not adopted technology as an effective sales tool. B&B Snack MSMEs face problems, namely a less strategic location and a lack of understanding of MSME owners regarding information technology. Therefore, in the YPPI Rembang University (UYR) Business Work Lecture Community Service activities, they provide a solution to overcome this problem, namely registering the location of MSME B&B Snacks on Google Maps and using direction signs, which can help customers find the location easily. The main goal is to increase the competitiveness of B&B Snack MSME owners in their main market in Rembang City and increase their business turnover. This activity began with a survey of MSME locations and discussions with B&B Snack MSME owners to identify problems. Furthermore, assisting MSMEs in registering locations on Google Maps and creating direction signs. The results of the activities of the MSME B&B Snack location are registered on Google Maps and have directional signs.